Association between restless legs syndrome and hypertension: a preliminary population‐based study in South Tyrol, Italy. (30th July 2013) - Giannini, G.; Zanigni, S.; Melotti, R.; Gögele, M.; Provini, F.; Facheris, M. F.; Cortelli, P.; Pramstaller, P. P.
<x xml:space="preserve">Abstract</x> Background and purpose Restless legs syndrome (RLS) is a sleep‐related movement disorder characterized by an irresistible urge to move the legs accompanied by paresthesia and/or dysesthesia that begins or worsens in the evening and night and that is partially or totally relieved by movement. Many studies have investigated the association between RLS and cardiovascular risk factors, particularly hypertension, leading to conflicting results. The aim of this study was to assess the association between RLS and hypertension considering also other cardiovascular risk factors that could act as confounders. Methods In all, 1709 participants of an on‐going adult population‐based study performed in South Tyrol, northern Italy, were enrolled. RLS was assessed through face‐to‐face interviews according to current International Restless Legs Syndrome Study Group diagnostic criteria. The presence of hypertension was self‐reported and determined by questionnaires administered by trained study nurses. Results The association between RLS and hypertension was not significant after adjustment for age, sex, diabetes mellitus, history of myocardial infarction, raised blood lipids and body mass index (odds ratio 1.24, 95% CI 0.85–1.80, P = 0.271). Conclusion Despite the small sample size of this study, RLS and hypertension were not associated in our adult population after adjustment for possible confounding factors. The presence of other cardiovascular risk factors could play a role as a confounder of this association.